Volcanic Plume Aging During Passive Degassing and Low Eruptive Events of Etna and Stromboli Volcanoes. Issue 21 (5th November 2019) - Pianezze, J.; Tulet, P.; Foucart, B.; Leriche, M.; Liuzzo, M.; Salerno, G.; Colomb, A.; Freney, E.; Sellegri, K.
Abstract: Volcanic gases and aerosols emissions from passive degassing or low eruptive events are now included in most climate models despite large uncertainties still exist about their injection height and their temporal and spatial variability. The aim of this study is to quantify the evolution of the gas and aerosols inside volcanic plumes with high kilometric‐resolution simulations. With online chemistry and aerosols, these simulations are carried out together with in situ measurements of aerosol and gas‐phase properties to assess the impact of Etna and Stromboli volcanic plumes produced by passive degassing and regular Strombolian activity, respectively. Comparison between simulation and observations show that the simulation reproduces the main characteristics of the volcanic plume evolution and confirms that volcanic plumes produced by passive degassing or low eruptive events have a strong impact on cloud condensation nuclei (CCN) formation increasing the number of CCN by a factor of 5. It was also shown that depending on the plume location, the aerosols will act as CCN at different distance from the vent. In the marine atmospheric boundary layer, the aerosols will act as CCN at proximity to the vent (less than 50 km) because of strong condensation sink inhibiting nucleation. In comparison, in the free troposphere, aerosols will act as CCN far from the vent, at more than 200 km. To the best of our knowledge, this study using in situ measurements as well as subkilometric simulations is unique. Key Points: Meso‐NH/SurfEx successfully simulates Etna and Stromboli volcanic plumes aging processes Simulations are evaluated through comparison with observations Volcanic plumes from passive degassing and low eruptive events significantly impact atmospheric CCN concentrations